Association Between Time From Stroke Onset and Fluid-Attenuated Inversion Recovery Lesion Intensity Is Modified by Status of Collateral Circulation. Issue 4 (April 2016) - Wouters, Anke; Dupont, Patrick; Christensen, Soren; Norrving, Bo; Laage, Rico; Thomalla, Götz; Albers, Greg; Thijs, Vincent; Lemmens, Robin
Abstract : Background and Purpose—: In patients with acute stroke, the intensity of a fluid-attenuated inversion recovery (FLAIR) lesion in the region of diffusion restriction is associated with time from symptom onset. We hypothesized that collateral status as assessed by the hypoperfusion intensity ratio could modify the association between time from stroke onset and FLAIR lesion intensity. Methods—: From the AX200 for ischemic stroke trial, 141 patients had appropriate FLAIR, diffusion-weighted imaging, and perfusion-weighted imaging. In the region of nonreperfused core, we calculated voxel-based relative FLAIR (rFLAIR) signal intensity. The hypoperfusion intensity ratio was defined as the ratio of the T max >10 s lesion over the T max >6 s lesion volume. A hypoperfusion intensity ratio threshold of ⩽0.4 was used to dichotomize good versus poor collaterals. We studied the interaction between collateral status on the association between time from symptom onset and FLAIR intensity. Results—: Time from symptom onset was associated with the rFLAIR intensity in the region of nonreperfused core ( B =1.05; 95% confidence interval, 1.0–1.1). We identified an interaction between this association and collateral status; an association was present between time and rFLAIR intensity in patients with poor collaterals ( r =0.53), but absent in patients with good collaterals ( r =0.17; P =0.04). Conclusions—: Our findings show that the relationship between time from symptom onset and rFLAIR lesion intensity depends on collateral status. In patients with good collaterals, the development of an rFLAIR-positive lesion is less dependent on time from symptom onset compared with patients with poor collaterals. Abstract : Supplemental Digital Content is available in the text.